NILAI-NILAI KULTURAL MAGISME TENGGER - Sri Mariati (Faculty of Humanities, Jember University, 2013)
This article aims at discussing the cultural values of magic in the context of Tenggerese culture. The research was ethnographivally done. The study results show that for the Tenggerese culture and society, spells and cultural values of magic represent a prayer. For the people holding mountainous culture, mantra and any of its kinds form a religious subculture whose ownership is controlled by shaman (dhukun pandhita). The Tenggerese culture regards dukun as a spearhead of the religious representation of Tenggerese community. Therefore, the practices of mantra use among the Tenggerese community are constructive in nature.Keywords: magical, spells, shaman, ritual, Tenggerese community